Strategi Pembinaan Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru Di SMPN 13 Kaur (Studi Kasus Di SMPN 13 Kaur) - Repulis; Sumarsih; Zakaria (UNIVERSITAS BENGKULU, 2023)
The purpose of this study was to describe the principal's coaching strategy in improving teacher professionalism in terms of planning, implementation and evaluation aspects of coaching. The research method uses descriptive qualitative. The research subjects were principals and teachers. Collecting data using observation, interviews and documentation. Data analysis using the Huberman model interactive technique went through three stages, data presentation, reduction, verification and conclusion. The results of the study indicate that the development planning is based on an analysis of teacher needs. self-evaluation of school potential. The implementation strategy is carried out through in-house training activities, teacher training, MGMP meetings, supervision of class visits. Evaluation of coaching is done by monitoring the success of teachers in compiling learning tools and supervising class visits to determine the success of teachers in improving their professionalism. Suggestions for principals to monitor on an ongoing basis by implementing programmatic teaching supervision involving senior teachers.